PENGARUH MODEL PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS VIII SMPN 30 TEBO - Helen, Aprimadedi; Nur Khasanah, Isnaeni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This research aimed to examine how eighth-grade students at SMP Negeri 30 Tebo reacted to the picture and picture learning model in an effort to enhance their descriptive writing skills. A somewhat unreliable experimental design was used for this study. This research was designed with a non-simultaneous control group. Students from eighth grade at SMP Negeri 30 Tebo made up the study's population. Sixty students were taken at random from two different sections of VIII: class VIII B (the experimental group) and VIII C (the control group). The control group receives instruction using a lecture format, while the experimental class is taught using a picture and picture model. The data collection tool consists of four essay questions. The data was analyzed using a t-test for independent samples. Both groups had similar averages on the pretest, with the test group averaging 55.13 and the control group averaging 60. Class A received a posttest average of 75.3% while Class B averaged 72.7%. At the 5% level of significance, the t-test on independent samples showed that the significance obtained was 0.01 0.05, so Ho was rejected and Ha was accepted. This research focuses on eighth-graders at SMP Negeri 30 in Tebo District, Indonesia, and how the picture and picture model can help them become better expository writers.